Microwave plasma-enhanced chemical vapour deposition growth of carbon nanostructures - Singh, Shivan R. (Academy of Science of South Africa, 2018)
The effect of various input parameters on the production of carbon nanostructures using a simple microwave plasma-enhanced chemical vapour deposition technique has been investigated. The technique utilises a conventional microwave oven as the microwave energy source. The developed apparatus is inexpensive and easy to install and is suitable for use as a carbon nanostructure source for potential laboratory-based research of the bulk properties of carbon nanostructures. A result of this investigation is the reproducibility of specific nanostructures with the variation of input parameters, such as carbon-containing precursor and support gas flow rate. It was shown that the yield and quality of the carbon products is directly controlled by input parameters. Transmission electron microscopy and scanning electron microscopy were used to analyse the carbon products; these were found to be amorphous, nanotubes and onion-like nanostructures.